Greatest show on earth: The evidence for evolution - Dawkins, Richard (London : Transworld Publishers, 2009)
Sifting through rich layers of scientific evidence, this is a counterattack on advocates of intelligent design, explaining the evidence for evolution while exposing the absurdities of the creationist argument.
Unabridged.
Includes bibliographical references and index
Read by Richard Dawkins
Keywords: Evolution (Biology); Biology